Łaska Boża i jej nieodzowna pomoc w utrzymaniu nadziei w codziennym życiu człowieka na przykładzie pism Paulina z Noli - Pałucki, Jerzy (Vox Patrum, 2018)
Letters and songs of Paulinus of Nola († 431) require a reader to be keen, careful and critical to the content its carries, specifically from the dogmatic point of view. Paulinus differentiates God’s the Father Grace, Christ’ Grace, Grace given by the Holy Spirit and finally grace received by people through the intercessions of saints. He never questions the dogma of the Trinity, but he is nonetheless criticised by Hieronymus as being too general in his writings, especially in poems. It is important to note that grace (gratia) as perceived by Paulinus of Nola does not only mean sacramental grace, but also the gift that allows one to uphold the virtue of hope and to grow spiritually and intellectually. In addition, the friendship and help given to a friend is a gift from God and manifestation of His grace.